A phase II, multicenter, open-label, randomized trial of pegfilgrastim for patients with alcohol-associated hepatitis. (December 2022) - Tayek, John A.; Stolz, Andrew A.; Nguyen, Danh V.; Fleischman, M. Wayne; Donovan, John A.; Alcorn, Joseph M.; Chao, Daniel C-K.; Asghar, Aliya; Morgan, Timothy R.; ,; Birudaraju, Divya; Botwin, Greg; et al.
Summary: Background: In trials conducted in India, recombinant granulocyte colony stimulating factor (GCSF) improved survival in alcohol-associated hepatitis (AH). The aim of this trial was to determine the safety and efficacy of pegfilgrastim, a long-acting recombinant GCSF, in patients with AH in the United States. Methods: This prospective, randomized, open label trial conducted between March 2017 and March 2020 randomized patients with a clinical diagnosis of AH and a Maddrey discriminant function score ≥32 to standard of care (SOC) or SOC+pegfilgrastim (0.6 mg subcutaneously) on Day 1 and Day 8 (clinicaltrials.gov NCT02776059). SOC was 28 days of either pentoxifylline or prednisolone, as determined by the patient's primary physician. The second injection of pegfilgrastim was not administered if the white blood cell count exceeded 30, 000/mm 3 on Day 8. Primary outcome was survival at Day 90. Secondary outcomes included the incidence of acute kidney injury (AKI), hepatorenal syndrome (HRS), hepatic encephalopathy, or infections. Findings: The study was terminated early due to COVID19 pandemic. Eighteen patients were randomized to SOC and 16 to SOC+pegfilgrastim. All patients received prednisolone as SOC. Nine patients failed to receive a second dose of pegfilgrastin due to WBC > 30, 000/mm 3 on Day 8. Survival at 90 days was similar in both groups (SOC: 0.83 [95% confidence interval [CI]: 0.57–0.94] vs. pegfilgrastim: 0.73 [95% CI: 0.44–0.89]; p > 0.05; CI for difference: -0.18–0.38). The incidences of AKI, HRS, hepatic encephalopathy, and infections were similar in both treatment arms and there were no serious adverse events attributed to pegfilgrastim. Interpretation: This phase II trial found no survival benefit at 90 days among subjects with AH who received pegfilgrastim+prednisolone compared with subjects receiving prednisolone alone. Funding: was provided by the United States National Institutes of Health and National Institute on Alcohol Abuse and Alcoholism U01-AA021886 and U01-AA021884.